2019
DOI: 10.1007/s00419-019-01589-y
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional elasticity analysis of sandwich panels with functionally graded transversely isotropic core

Abstract: In this paper, three-dimensional elastic deformation of rectangular sandwich panels with functionally graded transversely isotropic core subjected to transverse loading is investigated. An exponential variation of Young’s and shear moduli through the thickness is assumed. The approach uses displacement potential functions for transversely isotropic graded media and a three-dimensional elasticity solution for a transversely isotropic graded plate developed by the authors. The effects of transverse shear modulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…By employing the Hamilton principle in its analytical form, the three governing equations are developed as follows, Esmaeilzadeh and Kadkhodayan [37]; Mamen [30]: (13) In which 𝑡 1 and 𝑡 2 are the initial and end times, respectively.…”
Section: Governing Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…By employing the Hamilton principle in its analytical form, the three governing equations are developed as follows, Esmaeilzadeh and Kadkhodayan [37]; Mamen [30]: (13) In which 𝑡 1 and 𝑡 2 are the initial and end times, respectively.…”
Section: Governing Equations Of Motionmentioning
confidence: 99%
“…After their innovation in the late 90s, researchers carried out various investigations to assess the thermomechanical and dynamic behaviors of FGMs plates using different analytical methods [10][11][12][13][14]. Thai et al [2] confirmed that the FSDT is also accurate in investigating the free vibration analysis of FGM plates composed of functionally graded face sheets and an isotropic homogeneous core with variable thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The exact solution is given on a twoparameter basis by the displacement potential functions of a simply supported rectangular plate with constant yet arbitrary thickness. The assumptions of variance of Young's moduli (E) and shear moduli (G) [20] through the plates' thickness of plate has been examined. The strategy utilises displacement-based potential functions for transversely isotropic plates and 3-D elasticity solutions established.…”
Section: Introductionmentioning
confidence: 99%